Mixing of tree species is especially beneficial for biodiversity in fragmented landscapes, without compromising forest functioning. Issue 12 (27th September 2021) - Hertzog, Lionel R.; Vandegehuchte, Martijn L.; Dekeukeleire, Daan; Dekoninck, Wouter; de Smedt, Pallieter; van Schrojenstein Lantman, Irene; Proesmans, Willem; Baeten, Lander; Bonte, Dries; Martel, An; Verheyen, Kris; Lens, Luc
Abstract: Contemporary forest management strives to satisfy contrasting demands on forest ecosystems by promoting multiple ecosystem services. These services are affected in varied manners by alternative management actions operating at local or landscape scales, potentially leading to trade‐offs and synergies that may impede or encourage forest managers to change practices. We here studied ecosystem functions and biodiversity across trophic levels in 53 mature forest plots varying in stand‐level (tree species composition) and landscape‐level (degree of fragmentation) characteristics. The consequences of tree species composition and forest fragmentation for the provision of forest ecosystem services were explored using desirability scores, contrasting two different perspectives on forest management: a conservationist perspective placing more value on biodiversity conservation and a productivist perspective attaching more value to timber production and natural forest regeneration. These scores were derived at two spatial scales distinguishing between ecosystem functions and forest biodiversity. We show that more than two thirds of the 20 trade‐offs and synergies between functions and diversity variables were driven by variation in tree species composition and fragmentation. While multifunctionality depended on the forest management perspective at the stand level, this dependence was no longer apparent at the landscape scale. Interestingly, more strongly fragmented landscapes had higher landscape‐level multifunctionality, but this came at the expense of biodiversity across trophic levels. At the same time, mixed forest stands had higher levels of biodiversity than monocultures without affecting multifunctionality. Synthesis and applications . In monocultures, it depends on the management perspective as to which tree species best maximizes multifunctionality. However, diversifying stands resolves this potential tension between different perspectives; in mixtures the level of multifunctionality no longer depended on the management perspective and similar levels were reached compared to the monocultures. Tree species mixtures also maximized biodiversity across trophic levels. Diversifying forest stands thus represents a promising management strategy that resolves potential trade‐offs between functioning and biodiversity. Abstract : In monocultures, it depends on the management perspective as to which tree species best maximizes multifunctionality. However, diversifying stands resolves this potential tension between different perspectives; in mixtures the level of multifunctionality no longer depended on the management perspective and similar levels were reached compared to the monocultures. Tree species mixtures also maximized biodiversity across trophic levels. Diversifying forest stands thus represents a promising management strategy that resolves potential trade‐offs between functioning and biodiversity.